Evolving Trends of Button Battery Ingestion in Indian Children at a Tertiary Care Hospital. Issue 4 (7th April 2022) - Bettadahalli, Vishaka; Kumar, Sunil; Shukla, Indu; Nair, Rohini; Kumar, Poornima
Abstract : Introduction: Foreign body ingestion is a common problem encountered in the pediatric age group. Impaction of lithium batteries of greater than 20-mm diameter in the esophagus is associated with severe complications. This study aimed at analyzing the evolving trends of button battery ingestion in pediatric age groups at our tertiary care center in terms of clinical presentation, intraoperative findings, and the correlation of various clinical variables. Methods: A retrospective observational study was done. All children younger than 18 years with impaction of a button battery of size greater than 20 mm in the esophagus between January 2015 and December 2018 were included in the study. All children underwent removal of the battery using direct laryngoscopy/rigid esophagoscopy under general anesthesia. Results: There were 100 children included in the study with a mean age of 29.92 months having 93 children (93%) younger than 6 years. The mean duration of impaction was 34.7 hours. Increased duration of impaction was associated with an increased risk of complications and an increased difficulty in removal. There was a significant correlation between the site of impaction and the age of the patient. Complications were seen in 10% of cases with severe complications in 6 cases. No fatalities were reported in this study. Conclusions: Button batteries impacted in the esophagus can lead to severe complications including death. There has been an increasing trend in the ingestion of button batteries over the last 4 years. A prompt diagnosis and emergent removal of the battery are crucial to minimize the rate of complications. Symptoms of stridor and dysphagia must be given more attention, and these children are prioritized because they are more prone to have complications. Furthermore, primary prevention and caregiver education should be emphasized, and the need for a legislation to change the policies for securing the batteries in their products must be endorsed.